ANALYSIS OF BUSINESS MODEL DEVELOPMENT AT TUNAS BANGSA GUNUNG SAHARI CHRISTIAN ELEMENTARY SCHOOL USING BUSINESS MODEL CANVAS - Maruli Toga Mulia; A. Dewantoro Marsono (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
This study aims to map, evaluate, and improve the business model of Tunas Bangsa Gunung Sahari Christian Elementary School. The method used is qualitative, with data collection techniques through Focus Group Discussions (FGD) and in-depth interviews to gather information and analyze the business model. The subject of this research is Tunas Bangsa Gunung Sahari Christian Elementary School. The results of the study show that Tunas Bangsa Gunung Sahari Christian Elementary School has not fully implemented the Business Model Canvas approach. As a future business development effort, the nine elements in the Business Model Canvas were added and adjusted for the improvement of the existing business model. Additionally, the results of the SWOT analysis produced ten alternative strategies that can be used to support future business development.